Where does treatment optimism fit in? Examining factors associated with consistent condom use among people receiving antiretroviral treatment in Rio de Janeiro, Brazil - Hanif, Homaira (2014)
Johns Hopkins Bloomberg School of Public Health. Department of International Health. Social and Behavioral Interventions Program. Baltimore, MD, USA.